Students and Teachers Perception on the Use of Technology in English Learning at SMA Negeri 1 Telaga - Maga, Nazwa Natasya Keysha (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study investigates students and teachers perceptions of the use of technology in English learning at SMA Negeri 1 Telaga. The integration of digital tools such as YouTube, Duolingo, Grammarly, Lyrics Training, e-books, LCD projectors, Canva, and Quizizz has transformed English language instruction into a more interactive and engaging experience. The research aims to understand how both groups perceive the benefits, challenges, and effectiveness of technology in enhancing language skills and motivation. Employing a mixed-method approach, data were collected through questionnaires (involving 37 students and 5 teachers) and interviews (with 3 students and 2 teachers). The findings reveal that most teachers possess adequate technological proficiency and actively use various digital tools to support their teaching, although a few, particularly older teachers, face challenges due to limited experience and training. Students generally show a strong preference for technology-based learning, reporting increased motivation, engagement, and opportunities for independent learning. Nevertheless, several issues persist, including limited school infrastructure, inadequate access to stable internet, and distractions from social media. Despite these obstacles, the integration of technology is perceived as beneficial by both teachers and students, indicating a positive trajectory towards more dynamic and effective English language education. To maximize its impact, ongoing professional development for teachers and infrastructural improvements are essential.